Rail transport in Brazil: Challenges and opportunities - Alves, Edgard Gomes de Castro (2020)
The Brazilian Railway System emerged in 1854. At that time, railroad lines already had high expectations for the Brazilian economy. It can be understood that the Brazilian Railway Network is one of the main GDP of the country, with its exportation being one of the largest of all times. The option for this mode is significant for the flow of goods, especially when there are large volumes and long distances. In this article we will present the importance of this modal, its opportunities and challenges found in this operation, both in terms of logistics and infrastructure. To achieve the objective and demonstrate results, methods such as: bibliographic review methods, quantitative and qualitative analysis will be used for better credibility and reliability of the information.